A method for isolating highly purified and active mitochondria from insects. (July 2022) - Yang, Xiao-Jie; Zhao, Zi-Shun; Zhang, Yan-Mei; Ying, Jian-Ping; Wang, Su-Hao; Yuan, Ming-Long; Zhang, Qi-Lin
Graphical abstract: Highlights: Mitochondria are a key research target in insect physiology. A method for isolating highly purified mitochondria from insects was developed. This method could be widely applied in insects. Process to assess purity and activity of the isolated mitochondria was constructed. This method is effective for obtaining highly active mitochondria. Abstract: So far, methods that yield the high purity and activity of the isolated mitochondria from insects have not been reported and determined. Here, we develop methods that combine differential centrifugation and discontinuous Nycodenz density gradient centrifugation to isolate highly purified mitochondria from the thorax muscle of insects, and the methods were widely validated across three orders (Coleoptera, Hymenoptera, and Blattaria) covering four insect species using Western blot and transmission electron microscopy (TEM) analysis. The results showed the removal of the residual contamination with nonmitochondrial components such as nucleus, sarcolemma, cytosol, and endoplasmic reticulum. Furthermore, TEM, mitochondria staining, fluorescence detection, and flow cytometry analyses were employed to assess membrane integrity and activity of the isolated mitochondria. The results showed no loss of mitochondria activity/integrity after isolation. In addition, temporal dynamics in activity of the isolated mitochondria under commonly used laboratory temperature (-20 °C, 4 °C, and 25 °C) were respectively detected using a fluorescence microplate reader. The results showed that it should be avoided to store the isolated mitochondria at room temperature, and the mitochondria can meet the requirements of the most downstream experiments when they were stored at −20 °C. Overall, the study presented a method for isolating highly purified and active mitochondria from insects. This study firstly described a high-speed discontinuous density gradient centrifugation-based method that could be widely applied for mitochondria isolation in insects. The present study also provided an example to assess purity and integrity/activity of the isolated mitochondria.